2007
DOI: 10.1002/jcb.21416
|View full text |Cite
|
Sign up to set email alerts
|

Angiogenesis by transplantation of HIF‐1α modified EPCs into ischemic limbs

Abstract: Hypoxia inducible factor-1 alpha (HIF-1 alpha) is a key determinant of oxygen-dependent gene regulation in angiogenesis. HIF-1 alpha overexpression may be beneficial in cell therapy of hypoxia-induced pathophysiological processes, such as ischemic heart disease. To address this issue, human peripheral blood mononuclear cells (PBMNCs) were induced to differentiate into endothelial progenitor cells (EPCs), and then were transfected with either an HIF-1 alpha-expressing or a control vector and cultured under norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(45 citation statements)
references
References 32 publications
4
40
0
Order By: Relevance
“…Furthermore, it was observed that miR-138 negatively mediates levels of HIF-1α protein in EPCs, and overexpression of miR-138 was found to decrease hypoxia-induced HIF-1α expression in EPCs. Jiang et al (26) reported that HIF-1α overexpression promoted hypoxia-induced EPC differentiation, proliferation and migration. Therefore, the inhibitory effect of miR-138 overexpression on hypoxia-induced EPCs proliferation may occur by inhibiting the hypoxia-induced upregulation of HIF-1α expression.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it was observed that miR-138 negatively mediates levels of HIF-1α protein in EPCs, and overexpression of miR-138 was found to decrease hypoxia-induced HIF-1α expression in EPCs. Jiang et al (26) reported that HIF-1α overexpression promoted hypoxia-induced EPC differentiation, proliferation and migration. Therefore, the inhibitory effect of miR-138 overexpression on hypoxia-induced EPCs proliferation may occur by inhibiting the hypoxia-induced upregulation of HIF-1α expression.…”
Section: Discussionmentioning
confidence: 99%
“…Integrin b 1 was chosen for use in the present study in an effort to facilitate homing of the ECFCs to the ischemic tissue, which would be expected to abundantly express ECM. Although ECFCs have been genetically modified in a number of earlier studies, most of those involved overexpression of angiogenic factors (e.g., vascular endothelial growth factor, hypoxia inducible factor-1a, hepatocyte growth factor, or endothelial nitric oxide synthase) in an effort to strengthen or accelerate the angiogenic function of ECFCs, not to facilitate homing [27][28][29][30][31][32]. Our approach might be unique in that context.…”
Section: Discussionmentioning
confidence: 99%
“…While this work was in progress, several attempts to improve the efficacy of so-called ''endothelial progenitor cell'' therapy through expression of HIF-1␣, using vectors that were transduced by either electroporation (33) or adenoviral transduction (34), were reported. Although promising, these reports used the wild-type HIF-1␣ sequence, thus relying on continuous hypoxic culture to avoid degradation of HIF-1.…”
Section: Discussionmentioning
confidence: 99%